2007
DOI: 10.1071/ch07121
|View full text |Cite
|
Sign up to set email alerts
|

Radical Ring-Opening Polymerization of Phosphorus Heterocycles: Computational Design of Suitable Phosphetane Monomers

Abstract: High-level ab initio calculations have been used to determine the propensities of various phosphetanes towards radical ring-opening polymerization. At the G3(MP2)-RAD level of theory, the propagation rate constants of 1-methylphosphetane (7.5 × 10 4 L mol −1 s −1 ), 1-phenylphosphetane (4.6 × 10 5 L mol −1 s −1 ), cis,cis-2,4-dichloro-1-phenylphosphetane (3.8 × 10 7 L mol −1 s −1 ), cis,cis-2,4-difluoro-1-phenylphosphetane (3.0 × 10 7 L mol −1 s −1 ), and 1-phenyl-3-oxaphosphetane (4.0 × 10 6 L mol −1 s −1 ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It was found that, in the case of 1- tert -butylphosphetane, homolytic substitution of the propagating radical with tert -butyl substituents at phosphorus will be competitive with the propagation. The calculations also suggest that, for chiral phosphetanes, the ring-opening reaction is enantioselective at P and the polymer is expected to be isotactic …”
Section: Transition Metal Catalyzed Homogeneous Catalytic Reactions I...mentioning
confidence: 89%
See 1 more Smart Citation
“…It was found that, in the case of 1- tert -butylphosphetane, homolytic substitution of the propagating radical with tert -butyl substituents at phosphorus will be competitive with the propagation. The calculations also suggest that, for chiral phosphetanes, the ring-opening reaction is enantioselective at P and the polymer is expected to be isotactic …”
Section: Transition Metal Catalyzed Homogeneous Catalytic Reactions I...mentioning
confidence: 89%
“…The calculations also suggest that, for chiral phosphetanes, the ring-opening reaction is enantioselective at P and the polymer is expected to be isotactic. 172…”
Section: Homogeneous Catalysis Including 3-and 4-membered P-heterocyc...mentioning
confidence: 99%
“…Several ab initio studies have been reported that evaluate the feasibility of the radical ring-opening polymerization of several phosphorus-containing heterocycles. 82,83 Novel copper halide coordination polymers were prepared using a P 4 S 3 ligand. 84 Phosphonate-capped dendrimers have been prepared and were shown to promote the multiplication of human natural killer cells.…”
Section: ð15þmentioning
confidence: 99%
“…They show that ab initio quantum chemical calculations can be efficiently employed to predict a novel route to the radical ring-opening polymerization of phosphetanes to polyphosphines, with the aim of incorporating phosphorus atoms into polymer backbones to improve their polarity and metal-binding characteristics. [12] In an example of fundamental polymer physics in action, John Torkelson and his team investigate the effects of nanoscale confinement and interfaces on the glass transition temperature of poly(n-methacrylates). [13] The 29th APS and this special issue of Australian Journal of Chemistry thus demonstrate the importance of maintaining a balance as well as an efficient feedback loop between fundamental approaches and applications-(and sometimes commercially) driven research, focussing on fields such as polymer-based drug delivery, optoelectronics, or tissue engineering.…”
mentioning
confidence: 99%